Macroeconomic antecedents of racial disparities in psychiatric-related emergency department visits - Singh, Parvati (Frontiers in Psychiatry, 2024)
Objective: To test whether monthly declines in aggregate employment precede a rise in African American psychiatric-related ED visits (PREDVs) relative to white visits among low-income, working-age populations. Design: This study used repeated cross-sectional time series data for 6.7 million PREDVs among African Americans and white individuals from the State Emergency Department Database in 48 Metropolitan Statistical Areas (MSAs) across 4 states (Arizona, California, New York, New Jersey) from 2006 to 2011. MSA-level monthly employment data were obtained from the US Bureau of Labor Statistics. The outcome was specified as the race of a PREDV (African American = 1, white = 0). The exposure was operationalized as monthly percent change in MSA-level aggregate employment lagged by 0 to 3 months. Analysis included logistic regressions with county, month and year fixed effects, and clustered standard errors to examine the relation between odds of an African American PREDV (relative to white) following 0 to 3 months lag of MSA-level aggregate employment change. Findings: Logistic regression results indicate that the odds of PREDVs for publicly insured, working-age African Americans (relative to white individuals) increase three months after ambient employment decline (OR: 0.994, 95% CI: [0.990 0.998]). Conclusion: Economic downturns may marginally increase psychiatric help-seeking in EDs among publicly insured (low-income), working-age African Americans relative to white individuals. Findings from this study may contribute to the theoretical understanding of dynamic drivers of racial disparities in psychiatric ED visits.